1996
DOI: 10.1021/cm950317b
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification Studies of Polyimide Films Using Rutherford Backscattering and Forward Recoil Spectrometry

Abstract: We followed the surface imide ring hydrolysis of fully imidized polyimide films by aqueous base solutions using Rutherford backscattering spectrometry. The hydrolysis reaction was studied using several different polyimide films including spuncast and thermally imidized PMDA-ODA, Kapton-H, and Upilex-S films. The boundary between the modified layer at the surface and the underlying film is a sharp front behind which the conversion of the polyimide into poly(amic acid) is complete and ahead of which there is alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…This explanation accounts for the differences that we observed concerning a larger experimental content of carbon and oxygen in relation to nitrogen when comparing the theoretical and Fig. 2(b) show agreement with the results published by Stoffel et al 9 and Lee et al, 7 who observed the conversion of surface polyimide film to poly(amide acid).…”
Section: A Nh 4 Oh Treatment Of Kaptonாsupporting
confidence: 92%
See 4 more Smart Citations
“…This explanation accounts for the differences that we observed concerning a larger experimental content of carbon and oxygen in relation to nitrogen when comparing the theoretical and Fig. 2(b) show agreement with the results published by Stoffel et al 9 and Lee et al, 7 who observed the conversion of surface polyimide film to poly(amide acid).…”
Section: A Nh 4 Oh Treatment Of Kaptonாsupporting
confidence: 92%
“…Characteristics absorption bands of the polyamide layer 18,19 occurred at 1667 and 1540 cm −1 , and the appearance of a N-H stretching absorption mode at about 3250 cm −1 was observed, giving further evidence that the imide ring had been hydrolyzed. As pointed out by Stoffel et al, 9 the modified layer should be penetrated by a subsequently deposited layer. This molecular interdiffusion should allow strong bonding to occur between layers, which is thus not susceptible to environmental degradation.…”
Section: A Nh 4 Oh Treatment Of Kaptonாmentioning
confidence: 91%
See 3 more Smart Citations